2016
DOI: 10.3390/ijms17111893
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamic and Kinetic Properties of 2-Hydroxypyridine/2-Pyridone Tautomerization: A Theoretical and Computational Revisit

Abstract: The gas-phase thermal tautomerization reaction between 2-hydroxypyridine (2-HPY) and 2-pyridone (2-PY) was investigated by applying 6-311++G** and aug-cc-pvdz basis sets incorporated into some density functional theory (DFT) and coupled cluster with singles and doubles (CCSD) methods. The geometrical structures, dipole moments, HOMO-LUMO energy gaps, total hyperpolarizability, kinetics and thermodynamics functions were monitored against the effects of the corrections imposed on these functionals. The small exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…The gas phase internal energy difference between the two tautomers is ∼0.7 kcal/mol in favor of the enol form (2-HPY), while in water an internal energy difference of 2.8 kcal/mol was reported in favour of 2-PY. In cyclohexane, both tautomer coexist in comparable concentration while the 2-PY is dominant in solid state and polar solvents [7].…”
Section: Tautomerism Influences Many Aspects Of Chemistry and Biologymentioning
confidence: 99%
“…The gas phase internal energy difference between the two tautomers is ∼0.7 kcal/mol in favor of the enol form (2-HPY), while in water an internal energy difference of 2.8 kcal/mol was reported in favour of 2-PY. In cyclohexane, both tautomer coexist in comparable concentration while the 2-PY is dominant in solid state and polar solvents [7].…”
Section: Tautomerism Influences Many Aspects Of Chemistry and Biologymentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 27, 2020. ; https://doi.org/10.1101/2020.10.24.353318 doi: bioRxiv preprint October 27, 2020 in water an internal energy difference of 2.8 kcal/mol was reported in favour of 2-PY. In cyclohexane, both tautomer coexist in comparable concentration while the 2-PY is dominant in solid state and polar solvents [10].…”
Section: Tautomerism Influences Many Aspects Of Chemistry and Biologymentioning
confidence: 99%
“…The gas phase internal energy difference between the two tautomers is circa 0.7 kcal/mol in favor of the enol form (2-HPY), while in water an internal energy difference of 2.8 kcal/mol was reported in favour of 2-PY. In cyclohexane, both tautomer coexist in comparable concentration while the 2-PY is dominant in solid state and polar solvents [10].…”
Section: Introductionmentioning
confidence: 99%
“…In [Ag(2-pyridone)NO 3 ] n complex, both N and O are connected to Lewis acids (H + and Ag + ) and also the C-C distances: 1.425-1.436Å; and C-O distances: 1.266-1.273 Å, give no clear clue about whether this is the keto-or enol-form. In fact, looking at Figure 5 it seems that it falls right in the area that could be considered to correspond to the transition state and indeed the transition state of the tautomerization has been shown theoretically to go through a similar dimerization [57].…”
Section: Analysis Of Molecular Packingmentioning
confidence: 80%
“…It has been agreed for quite some time that it is the 2-pyridone form and not the tautomer 2-hydroxy-pyridine that is the most stable form of this molecule in the solid state, but in the gas phase 2-hydroxy-pyridine is favored and in solution sometime delicate equilibriums exist [56,57]. Depending on substitution pattern, similar molecules may prefer either forms, but a search of the Cambridge Structure Database (CSD) showed that the 2-pyridone form is prevalent, as illustrated in the plot of C1-O1 versus C1-C2 shown in Figure 5.…”
Section: Tautomerism In 2-pyridone/2-hydroxy-pyridine Systemsmentioning
confidence: 99%